Fernando Camacho Padilla, Fernando Escribano Martín, Nadereh Farzamnia Hajardovom y José Luis Neila Hernández, coords. 2021. Miradas de Irán: historia y cultura. Madrid: Catarata. 284 pp. ISBN 9788413522333 - Ghasemi, Saeideh (El Colegio de México, 2022)
Fernando Camacho Padilla, Fernando Escribano Martín, Nadereh Farzamnia Hajardovom y José Luis Neila Hernández, coords. 2021. Miradas de Irán: historia y cultura. Madrid: Catarata. 284 pp. ISBN 9788413522333